Calculation of areas flooded in urban reservoirs of water supply - Silva, E. A. [UNESP]; Leonardi, F. [UNESP]; Pedrosa, M. M. [UNESP]; Puga, F. [UNESP]; Leonardi, V. S. S. [UNESP]; Liu, Y. M.; Fu, D.; Tong, Z. X.; Bao, Z. Q.; Tang, B. (Crc Press-taylor & Francis Group, 2016)
In 2014, Brazil suffered a long drought period. The unusual lack of rainfall has resulted in a decrease in the water levels over the main reservoirs in the country. In this sense, images from remote sensing and techniques of digital image processing can be used as a tool to monitor the water level decrease. Two images from LandSat-8 were used in this work. The images were obtained in June 2015 and the actual situation of the Billings and Guarapiranga reservoirs was shown. The MATLAB software together with the mathematical morphology's toolbox was used to detect and determine the area of the reservoirs. For this purpose, a routine was developed to filter, highlight, and threshold the image.